KEPUTUSAN PENINGKATAN HUBUNGAN BILATERAL REPUBLIK RAKYAT CINA ERA XI JINPING DI BIDANG EKONOMI DAN PERTAHANAN DENGAN PAKISTAN TAHUN 2013-2017 - Mega Oktarina Putri (HI 16 UMY, 2016)
This research focus on the increasing of foreign relation between People Republic of China in economic and defense with Pakistan in Xi Jinping Era 2013-2017. As the Presiden of People Republic of China since he was elected, Xi Jinping came to visit Pakistan and made some new foreign policies. This created the huge different increase of foreign relation that People Republik of China ever done with Pakistan before. With a qualitative approach, this research emphasizes the content analysis method. Framework in this research is a foreign policy decision making process based on William D. Coplin theory. Foreign policy of a state is an action or strategy to achieve their national interest. Based on this theory, foreign policy supported by three factors. Domestic Politic, Economy-Military condition, and International context. The result of this research indicate that the increasing of foreign relation between People Republic of China with Pakistan in Xi Jinping era is supported by what are written on poin IV and poin VIII set by 18th Communist Party of China National Congress in November 2012 to developt an open economy and national stability. Besides, Xi Jinping have a power a general secretary in the party. Becoming the biggest economic growth and facing an open economy with silk road across border makes People Republic of China have to maintain the peacefull international environment. Moreover, the silk road is bulid in Xinjiang as the region in western China with the never ending terrorism conflict by ETIM. Besides, the nuclear agreement between India and United State of America make People Republic of China aware of the impact to what they already build in Pakistan. All of these factors supported the increasing foreign relation of People Republic of China in economic and defense with Pakistan in Xi Jinping era 2013-2017. Keywords : People Republic of China, foreign relation, Pakistan, Xi Jinping era